2017
DOI: 10.1097/jte.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Assessments That Evaluate Clinical Decision Making, Clinical Reasoning, and Critical Thinking Changes After Simulation Participation

Abstract: Background and Purpose. Increasingly, simulation experiences are augmenting and replacing portions of classroom and clinical education time. The purposes of this systematic review were to (1) systematically review the literature to determine whether simulated experiences impact the development of clinical decision making (CDM), clinical reasoning (CR), or critical thinking (CT) in students in health professional educational programs, (2) assess the quality of evidence for the effectiveness of simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…They identified tools by examining papers that applied an experimental design and measured critical thinking on multiple occasions in undergraduate nursing and midwifery education [ 9 ]. Similarly, Macauley et al [ 10 ] systematically reviewed evaluations of clinical reasoning that were used as outcome measures, this time in examining simulation programs in any health profession. They also included broad outcome measures that did not necessarily focus on clinical reasoning (e.g., the physical therapy entry-level competency assessment, the Assessment of Physiotherapy Practice [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They identified tools by examining papers that applied an experimental design and measured critical thinking on multiple occasions in undergraduate nursing and midwifery education [ 9 ]. Similarly, Macauley et al [ 10 ] systematically reviewed evaluations of clinical reasoning that were used as outcome measures, this time in examining simulation programs in any health profession. They also included broad outcome measures that did not necessarily focus on clinical reasoning (e.g., the physical therapy entry-level competency assessment, the Assessment of Physiotherapy Practice [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Macauley et al [ 10 ] systematically reviewed evaluations of clinical reasoning that were used as outcome measures, this time in examining simulation programs in any health profession. They also included broad outcome measures that did not necessarily focus on clinical reasoning (e.g., the physical therapy entry-level competency assessment, the Assessment of Physiotherapy Practice [ 10 ]). In a recent scoping review, Daniel et al [ 5 ] expanded the scope to investigate approaches to clinical reasoning evaluation used in a range of settings (workplace-based, simulation-based, and non-workplace-based settings), rather than only outcomes-based research, but restricted their review to the evaluation of the clinical reasoning of medical students, residents, and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…In an umbrella review covering 25 systematic reviews and over 700 primary studies, Cant and Cooper (2017) found evidence that simulation supported psychomotor development and improved self-efficacy among pre-licensure nursing students and was equivalent or superior to other teaching strategies. Similarly, authors of a systematic review of 31 studies found moderate to strong evidence that simulation improves clinical decision-making, critical thinking, and clinical reasoning for healthcare students (Macauley et al, 2017). In seven of the quantitative studies in the previous review, simulation was found to be at least as effective as traditional learning.…”
Section: Backg Rou N Dmentioning
confidence: 92%
“…Although simulation decreases the gap between theory and clinical application (Tinnon & Newton, 2017), few researchers have investigated the effect of embedding simulation with traditional lectures to augment learning and enhance students' knowledge acquisition. Overall, when simulation was used to augment lecture, improvements in clinical decision-making, clinical reasoning, and critical thinking were observed (Macauley et al, 2017). Other reviews have also shown that integration of simulation into lecture improved knowledge, skills and confidence of healthcare students (Alanazi et al, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 93%
“…e objective questions are marked using the string matching method, while the essay questions are marked using the intelligent marking technology proposed in this paper. e administrator, as the system administrator, is responsible for the management of teachers, students, and classes [21][22][23][24]. e administrator in this system is equivalent to the position of the head of the teaching and research team and reviews the group papers completed by the teachers and approves them before submitting the papers to the system.…”
Section: Marking System Designmentioning
confidence: 99%